Emotional state of stress and coping strategies in newly-diagnosed hypertensive young adults; a descriptive study - Wan Omar, Wan Fatein Nabeila; Abdullah, Aszrin (2022)
Introduction: This study aims to evaluate the emotional state of stress and coping strategies in newly-diagnosed hypertension in young adults (YOH) according to the presence of emotional stress symptoms. Methods: In a cross-sectional study in Kuantan, Pahang, Malaysia, we evaluated one hundred and fifteen individuals aged between 18 to 45 years. Individuals who had never been diagnosed with hypertension and satisfied the systolic blood pressure reading of at least 140 mmHg and/or diastolic blood pressure of at least 90 mmHg were included. The stress state was assessed using the 21-items Depression Anxiety Stress Scale and the abbreviated Coping Orientation to Problems Experiences (Brief-COPE) Inventory. A stress domain score above 14 was considered abnormal. Results: There was no significant difference in age, systolic blood pressure, diastolic blood pressure, employment status, and education status between YOH with normal and abnormal stress levels. YOH with abnormal stress (n = 28, 24.4%) presented higher use of dysfunctional coping strategy which is behavioural disengagement (p = 0.016). However, they also used emotional-focused coping strategies including use of emotional support (p = 0.033), humor (p = 0.027) and religion coping (p = 0.007). Besides that, YOH with abnormal stress also displayed a higher planning score (p = 0.035) as a problem- oriented coping strategy. Conclusion: These findings suggested that YOH with higher stress tend to use less appropriate coping strategies. It is recommended to reinforce the adoption of problem-oriented strategies to deal with stress to avoid the detrimental effects of emotional coping on blood pressure levels.